Dampak kesulitan manajemen waktu terhadap pola tidur dan tingkat kecemasan pada mahasiswa semester 1 di ma’had putra kampus 3 uin malang - Maulana, Ahmed Akas (Maliki Interdisciplinary Journal, 2026)
First semester students residing at Ma’had Campus 3 of UIN Malang face intensive academic demands and mandatory dormitory activities, leading many of them to experience difficulties in managing their time effectively. These challenges contribute to disrupted sleep patterns and heightened levels of anxiety. This study aims to describe the relationship between time management difficulties, sleep quality, and anxiety levels among students, as well as to identify the adaptive strategies they employ in coping with these pressures. Using a qualitative approach, the study involved 43 participants selected through purposive sampling. Data were collected through in depth interviews, observations, and questionnaires, and analyzed using the thematic analysis model of Miles, Huberman, and Saldaña. The findings indicate that most students experience a dual burden from academic tasks and Ma’had activities, which leads to late bedtimes, irregular sleep schedules, physical fatigue, and increased academic anxiety. Internal factors such as overthinking and nighttime smartphone use further exacerbate sleep disturbances, while external pressures including academic workload, Ma’had regulations, and family expectations intensify anxiety. The study concludes that poor time management creates a reciprocal cycle between sleep disturbances and anxiety. Therefore, improving self regulation skills and promoting healthy sleep practices are essential to support students’ psychological well-being.